Severe Hypertriglyceridemia-Induced Acute Pancreatitis - Molnár, Gyula (Case Rep Gastroenterol, 2021)
The prevalence of familial hypercholesterolemia (FH) is about 1 in 200–500 in the general population, but approximately less than 1% of those affected are actually diagnosed. One of the most promising approaches to treat FH is utilizing human monoclonal antibodies. This is a case study describing a 47-year-old male patient who presented to the Emergency Department with acute abdominal pain caused by severe hypertriglyceridemia (HTG)-induced acute pancreatitis (AP). We report the steps necessary for establishing the right diagnosis and the management of HTG-induced AP, which are inevitable for the reduction of severity and mortality. This case study shows that hypercholesterolemia is an underdiagnosed and potentially lethal disease. Once diagnosed, all measures should be considered to control blood cholesterol and lipid levels. The decision to administer PCSK9 inhibitors should not be solely based on economical calculation, but rather individual factors should also be considered to weigh the risk/benefit ratio.